PERBANDINGAN PENDIDIKAN PROFESI DOKTER DI INDONESIA DAN AMERIKA SERIKAT - Zuhriana K. Yusuf; Taufiq Qurrohman; Arifin Suking; Sitti Roskina Mas (Equity In Education Journal, 2022)
Medical Education has its peculiarities, particularly in different countries. This study aims to explain the comparison of medical education in Indonesia and America. This comparison is explained from several aspects: the purpose of education, length of time to study, the peculiarities of the education system, curriculum and learning system, educational evaluation system, and the advantages of the education system. The results of the literature study show that each country has its advantages. In Indonesia, there is only one type of general practitioner. In America, there are two types of general practitioners. The length of time for completing medical education in Indonesia is faster than in America, but more cases of disease and learning facilities in America. It is hoped that there will be more centers of excellence for certain diseases in Indonesia, which will become a learning tool for medical students.